2020
DOI: 10.4317/jced.56981
|View full text |Cite
|
Sign up to set email alerts
|

Simulated root canals preparation time, comparing ProTaper Next and WaveOne Gold systems, performed by an undergraduate student

Abstract: Background The aim of this study was to compare the WaveOne Gold and ProTaper Next systems regarding the time spent preparing simulated canals performed by an inexperienced student. Material and Methods 0 simulated L-shaped canals were randomly divided into two groups (n = 40) and numbered in order of instrumentation. Canals were instrumented with WaveOne Gold (group 1) and ProTaper Next (group 2) systems. The effective instrumentation time and the number of instrumenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…A previous study by Conceição et al 14 examined and compared the WaveOne (WO) Gold and PTN systems in terms of the time taken by an inexperienced undergraduate student to organize simulated canals. Mohammadzade et al 15 compared dentinal micro-crack formation following root canal instrumentation with ProTaper Universal and WO rotary systems in straight and curved root canals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Conceição et al 14 examined and compared the WaveOne (WO) Gold and PTN systems in terms of the time taken by an inexperienced undergraduate student to organize simulated canals. Mohammadzade et al 15 compared dentinal micro-crack formation following root canal instrumentation with ProTaper Universal and WO rotary systems in straight and curved root canals.…”
Section: Introductionmentioning
confidence: 99%
“…12 ProTaper (PTN; Dentsply Tulsa Dental Specialties), consisting of three significant design features, has been introduced in the market, which further minimizes the engagement between the file and the dentin. 13 A previous study by Conceição et al 14 examined and compared the WaveOne (WO) Gold and PTN systems in terms of the time taken by an inexperienced undergraduate student to organize simulated canals. Mohammadzade et al 15 compared dentinal micro-crack formation following root canal instrumentation with ProTaper Universal and WO rotary systems in straight and curved root canals.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to be less prone to dentin removal during instrumentation [9], even in canals with high curvatures [10]. In addition, it enabled a faster canal preparation compared to other nickel-titanium (Ni-Ti) instrumentation systems, such as ProTaper Next [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the effect of operator experience using mechanized systems concluded that, despite the good performance obtained by inexperienced operators, the associated learning curve should be highlighted; they considered it a crucial factor for establishing the minimum amount of work required for students to obtain the necessary competence for independent professional practice [16,[23][24][25][26]. Regarding the use of reciprocating systems, characterized by a simple and safer protocol [4,11], there are still few studies that evaluate the quality of the treatments performed by inexperienced operators, such as, undergraduate students, and the extension of its learning curve.…”
Section: Introductionmentioning
confidence: 99%
“…The shaping procedure of root canals has significant effect on success of endodontic treatment. [1][2][3] icroorganisms, dentin chips, pulp tissue or irrigation solution may be extruded into the periapical tissues during the biomechanical preparation. 4 .The apical extrusion phenomenon may cause unwanted postoperative complications such as pain, periapical inflammation, delay of periapical healing, and edema.…”
Section: Introductionmentioning
confidence: 99%